2021
DOI: 10.5781/jwj.2021.39.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Solidification Cracking Susceptibility of the Weld Metal of Additively Manufactured 316L Stainless Steel

Abstract: In this study, the solidification cracking susceptibility of the weld metal of additively manufactured 316L stainless steel was investigated. Laser powder bed fusion was employed to fabricate rectangular specimens with a thickness of 4 mm, and Trans-Varestraint tests were performed to evaluate the weldability of the specimens. Subsequently, the maximum crack lengths were measured and used as indices of susceptibility. The results showed that the weld metal of additively manufactured 316L stainless steel had hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Moreover, the weld with STS 308L filler mostly consisted of the FCC phase, and the BCC peaks were frequently observed at 44.4°, 64.4°, and 81.9° in the weld. The weld of STS normally contains a small amount of δ-ferrite to prevent solidification cracking during welding [8-13]. The CoCrFeMnNi HEA filler reduced the BCC peak in the weld, and our previous study reported the single phase of FCC for the HEA weld using the STS 308L filler [34].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the weld with STS 308L filler mostly consisted of the FCC phase, and the BCC peaks were frequently observed at 44.4°, 64.4°, and 81.9° in the weld. The weld of STS normally contains a small amount of δ-ferrite to prevent solidification cracking during welding [8-13]. The CoCrFeMnNi HEA filler reduced the BCC peak in the weld, and our previous study reported the single phase of FCC for the HEA weld using the STS 308L filler [34].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, LNG is stored at high pressure and it is constantly loaded and unloaded, and the fatigue properties should be considered significantly. However, the welds of STS involve some δ-ferrite, which is used to prevent solidification cracking during welding [8][9][10][11][12][13]. An increasing δ-ferrite content is known to have a deleterious effect on the tensile and fracture resistance of the weld metal (WM) at cryogenic temperatures [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue is the most dominant type of failure in offshore structures. Th has two parts, namely crack initiation and crack propagation [44][45][46]. In analysis, the crack was defined as a region of completely damaged materia between the damage variables and the number of cycles to failure was defin tion as follows:…”
Section: Crack Initiationmentioning
confidence: 99%
“…Fatigue is the most dominant type of failure in offshore structures. The fatigue crack has two parts, namely crack initiation and crack propagation [44][45][46]. In the 3D fatigue analysis, the crack was defined as a region of completely damaged material.…”
Section: Crack Initiationmentioning
confidence: 99%
“…Iron-chromium (Fe-Cr) alloys with excellent creep strength and heat resistance are in the spotlight as materials that can replace austenitic stainless steel [13,14]. To utilize Fe-Cr alloys as nuclear materials, many studies have been conducted on the addition and content control of alloying elements, such as Cr, Si, Al, and Mo [15,16], including evaluating their weldability [17,18]. In addition, studies on the evaluation of microstructure behavior and mechanical properties of Fe-Cr-based alloys according to heat input have been published [19][20][21].…”
Section: Introductionmentioning
confidence: 99%